Scrum-Driven Quality Improvement: Mitigating Software Failures Effectively - Noreen Khalid (Spectrum of Engineering Sciences, 2025)
The pressure on developmental teams increases due to the technical advancement of 21st century, accomplishing the projects within specific time frame. Various Incremental development process initiated to achieve the growing customers’ demands. But it is a challenge for developers to opt the best methodology for quality enhancement of Software failure. During this process risk management, right product, time limitation and error rate should be kept in mind to avoid the risk of failure. In this study, one of the most famous agile methodologies, Scrum, was introduced to analyze the improvement of software failures. Through this analysis, we can suggest the implementation of Scrum for quality enhancement of software failures. For further study, researchers can work on Scrum flexibility and use of scrum model in all kind of software; also can work on scrum architecture to improve the performance and efficiency in software development management.